On the analytic solutions for squeezing flow of nanofluid between parallel disks - Hashmi, Meraj Mustafa Mustafa; Hayat, Tasawar; Alsaedi, Ahmed (Nonlinear Analysis: Modelling and Control, 2012)
This article investigates the magnetohydrodynamic squeezing flow of nanofluid between parallel disks. Governing partial differential equations are converted into ordinary differential system via similarity transformations. We employ homotopy analysis method (HAM) to construct analytic expressions of velocity, temperature and nanoparticles volume fraction. Convergence analysis is performed and optimal values of the convergence-control parameters are determined. The computations are validated with the built in routine for solving nonlinear boundary value problems via shooting technique through software Mathematica 8.0. The behaviors of key parameters such as suction/blowing parameter (A), squeeze parameter (S), Hartman number (M), Brownian motion parameter (Nb) and thermophoresis parameter (Nt) are thoroughly examined. It is seen that the parameters have a great impact on the concentration field for the suction flow when compared with the blowing case. An intensification in the Brownian motion and thermophoresis effects results in the appreciable increase in the temperature and nanoparticles concentration.
Keywords: squeezing flow; nanofluid; permeable disk; analytic solution; shooting method